2017
DOI: 10.1007/s10508-017-1093-3
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Masculinity Facial Preference Among Naturally Cycling, Pregnant, Lactating, and Post-Menopausal Women

Abstract: Women show cyclical shifts in preferences for physical male traits. Here we investigated how fertility status influences women’s facial masculinity preference in men by analyzing a large sample of heterosexual women (N = 3720). Women were regularly either cycling (in both low- and high-conception probability groups), lactating or were currently in a non-fertile state (pregnant or post-menopausal). Analyses simultaneously controlled for women’s age and sexual openness. Participants via two alternative forced ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 82 publications
2
37
2
Order By: Relevance
“…However, number of previous‐year sexual partners and age of first sexual intercourse is predicted by limb muscle volume, but not by fat‐free mass (Lassek & Gaulin, ). Relatedly, more masculine faces are more attractive to women, especially in the context of a ST relationship (Dixson et al, ; Johnston et al, ; Little et al, ; Marcinkowska et al, ; Puts et al, ; Thornhill & Gangestad, ; Valentine et al, ) and more masculine faces are related to unrestricted sociosexual attitudes and number of sexual partners (Arnocky et al, ; Boothroyd et al, ; Boothroyd et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…However, number of previous‐year sexual partners and age of first sexual intercourse is predicted by limb muscle volume, but not by fat‐free mass (Lassek & Gaulin, ). Relatedly, more masculine faces are more attractive to women, especially in the context of a ST relationship (Dixson et al, ; Johnston et al, ; Little et al, ; Marcinkowska et al, ; Puts et al, ; Thornhill & Gangestad, ; Valentine et al, ) and more masculine faces are related to unrestricted sociosexual attitudes and number of sexual partners (Arnocky et al, ; Boothroyd et al, ; Boothroyd et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…unrelated to global SOI or the three SOI sub-scales (Kandrik, Fincher, Jones, & DeBruine, 2014). Finally, one study found that women's preferences for facial masculinity were negatively associated with unrestricted sociosexual attitudes (Lee, Dubbs, von Hippel, Brooks, & Zietsch, 2014a), while another study reported a positive but weak association between SOI and women's facial masculinity preferences (Marcinkowska, Jasienska, & Prokop, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Null results have also been reported in several studies testing the Dual Mating Strategy hypothesis using between-subject comparisons of women's masculinity preferences [39,40,42,[49][50][51][52]. Given that between-subjects designs are likely to be ill equipped to test for hormonal regulation of mate preferences (see earlier discussion), these null results are more difficult to interpret, however [35].…”
Section: Methodological Problems With Previous Researchmentioning
confidence: 96%